Handbook of environmental sociology - Caniglia, Beth Schaefer; Jorgenson, Andrew; Malin, stephanie A.; Peek, Lori; Pellow, David N.; Huang, Xiaorui (Switzerland Springer Nature, 2021)
This handbook defines the contours of environmental sociology and invites readers to push boundaries in their exploration of this important subdiscipline. It offers a comprehensive overview of the evolution of environmental sociology and its role in this era of intensified national and global environmental crises. Its timely frameworks and high-impact chapters will assist in navigating this moment of great environmental inequality and uncertainty.